2020
DOI: 10.1002/bbb.2159
|View full text |Cite
|
Sign up to set email alerts
|

Is anaerobic digestion a feasible alternative to the combustion of olive mill solid waste in terms of energy production? A critical review

Abstract: The use of olive mill solid waste (OMSW) for energy production has been promoted mainly through combustion processes. However, the European Union promotes the substitution of combustion in favour of greener alternatives. Several publications have stated that the energy obtained from anaerobic digestion (AD) is a feasible waste-toenergy technology for OMSW. However, the question of which energetic method, AD or combustion, is better for the energetic valorisation of OMSW has lacked of a reliable energy balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Industrial waste can be a good option for AD due to its high content of organic matter. The organic content of industrial wastewater is reported to be 20-4400 times higher than the urban wastewater, with a methane production capacity of 34-572 mlCH 4 /gVS, depend upon the type of industry [106,107]. In contrast, the amount of nitrogen in industrial waste is low, so they have a high C/N ratio (17.5-49).…”
Section: Industrial Waste 331 Overall Process Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Industrial waste can be a good option for AD due to its high content of organic matter. The organic content of industrial wastewater is reported to be 20-4400 times higher than the urban wastewater, with a methane production capacity of 34-572 mlCH 4 /gVS, depend upon the type of industry [106,107]. In contrast, the amount of nitrogen in industrial waste is low, so they have a high C/N ratio (17.5-49).…”
Section: Industrial Waste 331 Overall Process Performancementioning
confidence: 99%
“…However, the presence of toxic compounds may limit the use of some industrial wastes. In addition, using more than the optimal amount of industrial waste in sewage sludge ACoD process leads to propionic acid accumulation which consequently causes a severe imbalance in the process [100,106,107]. For example, Fountoulakis et al [112] reported that adding 1-3% (v/v) crude glycerol to sewage sludge could damage the AD system due to overloading.…”
Section: Industrial Waste 331 Overall Process Performancementioning
confidence: 99%
“…It is worth noting that the present fungal treatment allowed the phenolic detoxification of the OMSW, but not the recovery of the valuable phenolic compounds. However, despite this drawback, the fungal treatment does not have high energy requirements in comparison with the thermal treatments proposed for the recovery of phenols [62]. Therefore, the proposed fungal treatments using A. discolor and S. hirsutum would be a suitable strategy for the detoxification of OMSW, allowing the subsequent valorization of this biomass without a high energy cost.…”
Section: Omsw Phenol Removal Using a Discolor And S Hirsutummentioning
confidence: 99%
“…Although three-phase decanters have the highest olive oil recovery efficiency, they produce the highest amount of waste streams [3]. After decades of substantial investments in the modernization of oil mills in order to reduce freshwater consumption and the quantity of olive mill waste streams, nowadays more than 90% of olive mills in Spain are based on the two-phase extraction process, which constitutes the main extraction system with over 95% of the total olive oil production [5]. However, the olive oil sector still faces additional challenges toward environmental sustainability concerning waste management and recovery, as well as energy efficiency improvement [6].…”
Section: Introductionmentioning
confidence: 99%